The Influence of Hyper Content-Based Practicum Guidance on Students' Scientific Literacy Ability in Material Structure and Function of Plant Tissues for Class XI IPA Students at SMA Negeri 2 Gowa (JED (Jurnal Etika Demokrasi), 2021)
This research is an experimental researchQuasi Experimental Design which aims to determine the effect of a practicum-based guidehyper content on the scientific literacy skills of class XI IPA students at SMA Negeri 2 Gowa on the material structure and function of plant tissue with a research design "Nonequivalent Control Group Design”. The population in this study was class XI IPA SMA Negeri 2 Gowa which consisted of six classes with a total of 151 students. The sample of this study consisted of two classes, namely class XI IPA 1 as an experimental class of 25 students and class XI IPA 2 as a control class of 25 students who were randomly selected.Simple Random Sampling. The research variables consist of independent variables, namely practicum-based guideshyper content while the dependent variable is scientific literacy ability. Data collection is done through givingpretest andposttest. Data were analyzed with descriptive statistics and inferential statistics with the help ofSPSS (Statistical Product and Service Solutions) versi 25. The results showed that the average value of the resultsposttest the experimental class is 71.33 and the control class is 54.73. In the hypothesis test throughIndependent Sample T- Test with a value of p = 0.000